SOSIALISASI PEMANFAATAN PELEPAH SAWIT SEBAGAI ALTERNATIF PAKAN TERNAK SAPI DI DESA MULYOHARJO KECAMATAN BTS ULU KABUPATEN MUSI RAWAS - Triyanti, Merti; Rozi, Zico Fakhrur (Universitas Muhammadiyah Tapanuli Selatan, 2021)
This Community Service Program is motivated by the large number of lands that have changed their function as both residential land and plantation land in the village of Mulyoharjo, especially oil palm plantations. The plantations produce palm oil waste which is largely unused, including oil palm fronds. In addition, the impact of these plantations is the reduction in open land used by cattle farmers as animal feed. Therefore the STKIP PGRI Lubuklinggau PKM Team tried to apply the use of palm fronds as an alternative to cattle feed. Palm fronds are one of the byproducts or can be said to be waste from oil palm plantations. The abundant amount of palm midrib can be used as animal feed. Palm midrib itself Has nutritional content that is 48.78% dry matter, crude protein 5.3%, hemicellulose 21.1%, cellulose 27.9%, crude fiber 31.09%, ash 4.48%, BETN 51.87 %, lignin 16.9% and silica 0.6%. This activity has been carried out by involving partners namely the people of Mulyoharjo Village and was followed with enthusiasm. The output targets to be achieved by the PKM team are the improvement of community values and publications. In practice, using theoretical and practical methods begins with the preparation, material and practice of making cattle feed from palm fronds.